2012
DOI: 10.1007/s11926-012-0293-z
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medicine for Rheumatic Diseases: Promises Kept?

Abstract: Traditional healers throughout the world have relied on herbal medicines in their practices for millennia to treat a wide array of conditions, including arthritis. Present-day patients continue to seek care from complementary and alternative providers and more effective and less toxic treatments. A broad foundation of laboratory studies suggests that many herbal products have pertinent medicinal effects for the management of diseases like osteoarthritis and rheumatoid arthritis. However, few high quality clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…However, it might not directly affect HILI because it has been generally used in many herbal formulas to mediate other herb functions and properties as well as to exert a protective effect on liver injury (Chen et al, ; Ji et al, ; Jung et al, ). To our knowledge, herbal medicines in our HILI cases are not generally used in the treatment of RD (Ernst, ; Kolasinski, ; Setty & Sigal, ). Moreover, different types of herbal medicines can be diversely prescribed in clinical practice depending on the characteristics of patients with RD.…”
Section: Discussionmentioning
confidence: 99%
“…However, it might not directly affect HILI because it has been generally used in many herbal formulas to mediate other herb functions and properties as well as to exert a protective effect on liver injury (Chen et al, ; Ji et al, ; Jung et al, ). To our knowledge, herbal medicines in our HILI cases are not generally used in the treatment of RD (Ernst, ; Kolasinski, ; Setty & Sigal, ). Moreover, different types of herbal medicines can be diversely prescribed in clinical practice depending on the characteristics of patients with RD.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prevalence of self‐reported adverse events in our study was low (3%), patient safety is still a concern as patients may not associate experienced symptoms as adverse effects, and previous studies suggest that most patients do not feel comfortable reporting potential adverse events associated with s‐NHP use to healthcare providers (Ramos‐Remus & Raut, ; Walji et al, ). High‐quality clinical studies demonstrating efficacy and safety are lacking for most, if not all, s‐NHPs, and their adverse effect profiles and potential for drug interactions are not well known (Kolasinski, ; Kutt et al, ; Setty & Sigal, ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increasing acceptance of complementary and alternative medicines (CAMs) by conventional care providers, NHPs remain an overlooked aspect of patient medication history (Manek et al, ; Ramos‐Remus et al, ; Ramos‐Remus, Watters, Dyke, Suarez‐Almazor, & Russell, ; Rao, Kroenke, Mihaliak, Grambow, & Weinberger, ; Wu, Wang, Tsai, Huang, & Kennedy, ). Although historical data have shown that CAM users in the general population are more likely to be female, middle‐aged and college educated, previous research among rheumatology patients has not identified consistent predictors of NHP use (Ernst, ; Kolasinski, ; Ramos‐Remus & Raut, ; Ramos‐Remus et al, ; Rao et al, ). The focus of these studies has been broad, and the results variable, but few have looked at patient reports of symptomatic improvement on NHPs, and data specific to patients with inflammatory arthritis are scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an intervention that helps to decrease blood glucose levels and potentially increase or prevent losses in functional β-cell mass would be of clinical use to prevent, delay, or even assist in treating diabetes. A number of herbal remedies have been used throughout history to treat a variety of human diseases, including diabetes mellitus [12][13][14]. Although there are herbal drugs approved for use in China that are effective in lowering blood glucose levels [15], few clinical trials using herbal based approaches have been carried out in Western countries.…”
Section: Introductionmentioning
confidence: 99%